Phenomenon of Urban Agriculture and Its Role in Shaping Sustainable Cities - Dorofieieva, Kateryna; Vugule, Kristīne (Landscape Architecture and Art, 2021)
The rapid growth and development of the world have lead to significant changes in the expansion of urban sprawl, land distribution, and the general functioning model of modern cities. The problems connected to ecology, economy, human physical and mental well-being become more urgent with every day under the influence of arising deficiency of open green spaces, nutritional security, and sustainable financial models for small-scale businesses within the cities; and not only affect regular citizens but also general tendencies of urban and landscape planning that are supposed to deal with those issues. One of the tools aimed at combating them for the past decades has been an increasingly popular urban agriculture, particularly chosen as a studying object of interest for this publication. The following paper represents complex research conducted in an integrated manner by reviewing the overall phenomenon of urban agriculture and its pioneering practices; determining the key components of their successful functioning and positive ways of affecting surroundings; and consequently forming the list of concluding recommendations for planning and management of such structures. As the main methods of research, the selective case study, describing principal features of such initiatives, and relevant literature analysis for the fundamental information gathering were applied by the author. The results of the research were composed into the summarizing table highlighting core data and supporting developed conclusion based on examination and designing suggestion for interested parties.